2004
DOI: 10.1186/1741-7007-2-12
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional organization of telomeres in the nucleus of mammalian cells

Abstract: Background: The observation of multiple genetic markers in situ by optical microscopy and their relevance to the study of three-dimensional (3D) chromosomal organization in the nucleus have been greatly developed in the last decade. These methods are important in cancer research because cancer is characterized by multiple alterations that affect the modulation of gene expression and the stability of the genome. It is, therefore, essential to analyze the 3D genome organization of the interphase nucleus in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 31 publications
4
68
0
Order By: Relevance
“…Telomere clustering was detected in both undifferentiated and terminally differentiated cells. It seems that this is a characteristic feature of interphase nuclei arrangements, since it was observed in many cell types, including lymphocytes, neutrophils, and cancer cells (Chuang et al 2004;Weierich et al 2003;Yerle-Bouissou et al 2009). Since mammalian HP1α localizes with pericentromeric heterochromatin in the interphase, we also analysed the distribution of chromocenters.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere clustering was detected in both undifferentiated and terminally differentiated cells. It seems that this is a characteristic feature of interphase nuclei arrangements, since it was observed in many cell types, including lymphocytes, neutrophils, and cancer cells (Chuang et al 2004;Weierich et al 2003;Yerle-Bouissou et al 2009). Since mammalian HP1α localizes with pericentromeric heterochromatin in the interphase, we also analysed the distribution of chromocenters.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere measurements were done with TELOVIEW (9,46). By choosing a simple threshold for the telomeres, a binary image is found.…”
Section: D Image Analysis For Telomeresmentioning
confidence: 99%
“…We recently reported that the normal interphase nucleus has a unique 3D telomeric organization that is cell cycle dependent (9,10). Telomeres are organized in a nonoverlapping manner and align into a central telomeric disk during the late G 2 phase of the cell cycle (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent trend to record and analyze the early genomic events associated with transition through telomere crisis and aggregation is, detection of telomeric FISH signals using 3D epifluorescent or confocal laser scanning microscopes with adjusted fluorescence standard. Telomeric aggregates are suggestive of genomic instability and it is possible to examine the aggregates in individual interphase nuclei and tissues without the need to examine metaphases [76]. The next step is to analyze the 3D images visually and also by using specially designed software for quantitation [40,76].…”
Section: Future Directions In the Study Of Telo-meres In Breast And Omentioning
confidence: 99%